Film Islami Sebagai Model Interpretasi atas Al-Qur'an dan Hadis: Kasus Film Ayat Tentang Cinta - Mila Aulia; Miski Miski (Jurnal Theologia, 2020)
This paper analyzes the movie Ayat tentang Cinta, which still has not received much attention from the researchers, namely from the aspect of the existence of the Qur'anic verses and traditions in it. Two core questions want to be the focus of the study, first, how does the movie Ayat tentang Cinta position the Qur'an [and hadith] as a representation of an interpretation of the Qur'an and hadith? Secondly, how is the existence of the values of the Qur'an [and hadith] in the film being one of the concourses of righteousness? This paper is a qualitative study, using content analysis and a semiotic approach. The results of this study show that in the movie Ayat tentang Cinta, it appears how the scenes displayed by the actors can show the relevant point of a movie as an interpretation of the Qur'an and Hadith, for example, the cafeteria in marriage is allegedly based on the QS. Al-Nur: 26. Secondly, in the movie Ayat tentang Cinta, many of the values of the Qur'an and Hadith in its diverse form, such as how each central figure in the movie describes the things that are relevant to the values of the Qur'an and hadith, at least through the distinctive scenes. All of this, as well as being one of the interesting facts about the construction efforts of righteousness by actors into the minds of audiences. Of course, in typical terminology.